How do age and social environment affect the dynamics of death hazard and survival in patients with breast or gynecological cancer in France?. Issue 2 (25th September 2021) - Poiseuil, Marie; Tron, Laure; Woronoff, Anne‐Sophie; Trétarre, Brigitte; Dabakuyo‐Yonli, Tienhan Sandrine; Fauvernier, Mathieu; Roche, Laurent; Dejardin, Olivier; Molinié, Florence; Launoy, Guy; ,
Abstract: Several studies have investigated the association between net survival (NS) and social inequalities in people with cancer, highlighting a varying influence of deprivation depending on the type of cancer studied. However, few of these studies have accounted for the effect of social inequalities over the follow‐up period, and/or according to the age of the patients. Thus, using recent and more relevant statistical models, we investigated the effect of social environment on NS in women with breast or gynecological cancer in France. The data were derived from population‐based cancer registries, and women diagnosed with breast or gynecological cancer between 2006 and 2009 were included. We used the European deprivation index (EDI), an aggregated index, to define the social environment of the women included. Multidimensional penalized splines were used to model excess mortality hazard. We observed a significant effect of the EDI on NS in women with breast cancer throughout the follow‐up period, and especially at 1.5 years of follow‐up in women with cervical cancer. Regarding corpus uteri and ovarian cancer patients, the effect of deprivation on NS was less pronounced. These results highlight the impact of social environment on NS in women with breast or gynecological cancer in France thanks to a relevant statistical approach, and identify the follow‐up periods during which the social environment may have a particular influence. These findings could help investigate targeted actions for each cancer type, particularly in the most deprived areas, at the time of diagnosis and during follow‐up. Abstract : What's new? Several studies have investigated the association between net survival and social inequalities in cancer, highlighting a varying influence of deprivation depending on the cancer type. Here, using a new statistical approach with flexible modelling via penalised splines, the authors show a substantial effect of social environment on net breast cancer and cervical cancer survival. In addition, their results reveal the complex effects of deprivation on survival in corpus uteri and cervical cancer, such as time‐dependent effects and age interactions. The findings could help investigate targeted actions, particularly in the most deprived areas, at the time of diagnosis and during follow‐up.